2013
DOI: 10.1371/journal.pone.0059234
|View full text |Cite
|
Sign up to set email alerts
|

Acute Colitis Induces Neurokinin 1 Receptor Internalization in the Rat Lumbosacral Spinal Cord

Abstract: Substance P (SP) and its receptor, the neurokinin 1 receptor (NK1R), play important roles in transmitting and regulating somatosensory nociceptive information. However, their roles in visceral nociceptive transmission and regulation remain to be elucidated. In the previous study, moderate SP immunoreactive (SP-ir) terminals and NK1R-ir neurons were observed in the dorsal commissural nucleus (DCN) of the lumbosacral spinal cord. Thus we hypothesized that the SP-NK1R system is involved in visceral pain transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
1
11
0
7
Order By: Relevance
“…Subsequently, a polyethylene tube, which was wrapped in surgical tape at ~30 mm from the edge, was inserted through the anus. A 5% formalin solution or saline (100 µl) was injected through the tube slowly to prevent leakage (15).…”
Section: Animalsmentioning
confidence: 99%
“…Subsequently, a polyethylene tube, which was wrapped in surgical tape at ~30 mm from the edge, was inserted through the anus. A 5% formalin solution or saline (100 µl) was injected through the tube slowly to prevent leakage (15).…”
Section: Animalsmentioning
confidence: 99%
“…We validated this method by comparing it to conventional immunoassay measures of substance P release and found that it has higher sensitivity (Marvizon et al, 2003a). In addition, NK1R internalization can be measured non-invasively in vivo (Mantyh et al, 1995, Allen et al, 1997, Honore et al, 1999, Kondo et al, 2005, Adelson et al, 2009, Zhang et al, 2010b), allows the spatial location of substance P release (Abbadie et al, 1997, Allen et al, 1999, Hughes et al, 2007, Zhang et al, 2013) and measures substance P release at physiologically relevant concentrations that activate the NK1R (Trafton et al, 1999). NK1R internalization may also detect the release of neurokinin A, but not the release of neurokinin B.…”
mentioning
confidence: 99%
“…Although multiple studies have investigated substance P release in inflammatory conditions (Abbadie et al, 1997, Allen et al, 1999, Honore et al, 1999, Honore et al, 2002, Zhang et al, 2013), just a few of them have investigated how it is affected by nerve injury. These studies have centered primarily on the type of primary afferents (i.e., Aβ-, Aδ-of C-fibers) that release substance P after nerve injury (Allen et al, 1999, Malcangio et al, 2000, Hughes et al, 2007) and have not investigated changes in the pharmacological modulation of substance P release.…”
mentioning
confidence: 99%
“…, 50 μg, 10 min before SP injection; 81.62 ± 2.86%, F = 1.201, P = 0.828; Figure 7C) but was decreased by L732138 ( i.t. , 100 nM, 10 min before SP injection; Cahill and Coderre, 2002; Zhang et al, 2013; Figure 7D). These results indicated that EM2 had no direct effects on NK1R internalization.…”
Section: Resultsmentioning
confidence: 94%
“…In lamina I of the SDH, the NK1R-positive neurons that included the nucleus and a large area of cytoplasm were selected. NK1R-positive neurons with 10 or more endosomes in the soma were considered as internalized neurons (Zhang et al, 2013). The ability of NK1R internalization was represented as the proportion of NK1R-internalized cells (NK1R-internalized cells/NK1R-positive cells).…”
Section: Methodsmentioning
confidence: 99%